Early effect of boron neutron capture therapy mediated by boronophenylalanine (BPA-BNCT) on mast cells in premalignant tissue and tumors of the hamster cheek pouch - Aromando, Romina Flavia (2010)
Mast cell (MC) activation in the hamster cheek pouch cancerization model is associated with the increase in tumor cell proliferation, mediated in turn by tryptase, a protease released from mast cell granules after activation. Tryptase induces tumor cell proliferation through the activation of PAR-2 (protease activated receptor-2) on the plasma membrane of carcinoma cells. The therapeutic success of boron neutron capture therapy mediated by boronophenylalanine (BPA-BNCT) in tumor control in the hamster cheek pouch oral cancer model has been previously reported by our laboratory. Early effects of BPA-BNCT on tumors of the hamster cheek pouch include a reduction in DNA-synthesis with the concomitant decrease in the proliferation of malignant cells. The aim of the present study was to investigate the early histological changes in mast cells after BPA-BNCT in tumors and premalignant tissue of the hamster cheek pouch. Tumor-bearing pouches were treated with BPA-BNCT or beam only (neutron irradiation without prior administration of the boron compound) and sacrificed 1 day after treatment. The samples were fixed in Carnoy fixative and stained with alcian blue-safranin to identify all the populations of mast cells. Total, active and inactive mast cells (MC) were counted in the connective tissue and the adventitious tissue underlying the pouch wall and at the base of the tumors in pouches treated with BPA-BNCT, in keeping with a previously described technique. BPA-BNCT induced a marked reduction in the total number of mast cells in the pouch (p < 0.05). This reduction in the total number of mast cells was due to a reduction in mast cells at the base of the tumor (p < 0.005) and it occurred at the expense of the active mast cells (p < 0.05). A slight reduction that did not reach statistical significance also occurred in the amount of mast cells in the pouch wall (that corresponds to the premalignant tissue in tumor-bearing pouches), and in the adventitious tissue. In this case the reduction was seen in the inactive population. Both BPA-BNCT and beam only elicited a qualitative change in the secretion modality of the granule content. Although further studies are needed to evaluate the subcellular effect of BNCT on mast cell granule secretion, the reduction in cell proliferation induced by BPA-BNCT would be partially due to the decrease in total mast cells in the hamster check pouch.